Pengembangan Media Miniatur Diorama Siklus Air pada Mata Pelajaran IPAS SD - Oktaviani, Siti Nur; Faradita, Meirza Nanda; Martati, Badruli (Jurnal Simki Pedagogia, 2025)
The research is to develop a miniature diorama media product of the water cycle for science learning that has quality in terms of practical validity and effectiveness. This research uses the development method (RnD), this development uses the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SD Kyai Abdullah Ubaid 1 Surabaya, with the research subjects being 37 fifth grade students. The research was conducted in October - November 2024. Data collection techniques used questionnaires and tests. The research instruments were in the form of validation sheets for experts and materials, teacher response questionnaire sheets and student questionnaire sheets, and test sheets. This research produced a miniature diorama media of the water cycle that obtained very valid criteria with a percentage reaching 97.5% in media expert validation, while the results of material expert validation obtained a percentage of 96.66%. The results of practicality were seen from the teacher questionnaire response sheet of 96% and students obtained 90% with the category "very practical". The results of the effectiveness test showed a value of 86.83% with the category of "effective" based on the level of student learning completion. It can be concluded that this water cycle diorama miniature media product meets the criteria of valid, practical and effective.